2017
DOI: 10.3892/ijmm.2017.3156
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Bcl-2-shRNA expression vector and its effect on the mitochondrial apoptosis pathway in SW982 cells

Abstract: Apoptosis is considered to serve an important role in the pathogenesis of rheumatoid arthritis. The aim of the present study was to construct Bcl-2-short hairpin (sh)RNA expression vectors and transfect them into human synovial sarcoma SW982 cells, in order to screen for an effective interference sequence and analyze the effects of this interference on the expression levels of Bcl-2 and other molecules associated with the mitochondrial apoptosis pathway. Three different shRNAs (Bcl-2-sh1, 2 and 3) were designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…Studies have shown that STAT5 induces the expression of Bcl-2, Bcl-xL, IL-2 and IL-1 [17][18][19] . Anti-apoptotic factors Bcl-2 and Bcl-xL inhibit the apoptosis of RA-FLS by regulating the activities of Caspase-3 and other proteins related to cell proliferation and apoptosis [20][21][22] . Interleukin (IL) 2 is a soluble T cell growth factor that regulates the proliferation and differentiation of T cells and promotes the progression of systemic autoimmune diseases by binding to high-a nity receptor subunits.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that STAT5 induces the expression of Bcl-2, Bcl-xL, IL-2 and IL-1 [17][18][19] . Anti-apoptotic factors Bcl-2 and Bcl-xL inhibit the apoptosis of RA-FLS by regulating the activities of Caspase-3 and other proteins related to cell proliferation and apoptosis [20][21][22] . Interleukin (IL) 2 is a soluble T cell growth factor that regulates the proliferation and differentiation of T cells and promotes the progression of systemic autoimmune diseases by binding to high-a nity receptor subunits.…”
Section: Discussionmentioning
confidence: 99%
“…B-cell lymphoma-2 (Bcl-2) family proteins are key regulators of programmed cell death (Tsujimoto, 1998;Zhang et al, 2017). More specifically, Bcl-2 proteins control the intrinsic apoptotic pathway.…”
Section: B-cell Lymphoma-2 Proteinsmentioning
confidence: 99%
“…Apoptotic signals, like temperature variations, exposure to hydrogen peroxide and pH perturbations, induce mitochondrial outer-membrane permeabilization by triggering Bax. Consequently, cytochrome C is released leading to apoptotic cell death by activating cysteine proteases (Li et al, 1997;Zhang et al, 2017).…”
Section: B-cell Lymphoma-2 Proteinsmentioning
confidence: 99%
“…Therefore, they have attracted the attention of scholars at home and abroad 5 . At present, the antitumor mechanism of action of active peptides can be divided into two types: one is mediated by direct action on tumor cells, such as inhibiting tumor cell proliferation and inducing tumor cell apoptosis, and the second is mediated by indirect effects on tumor cells, such as by regulating the body's immune function and inhibiting tumor angiogenesis, among other ways 6‐8 …”
Section: Introductionmentioning
confidence: 99%
“…5 At present, the antitumor mechanism of action of active peptides can be divided into two types: one is mediated by direct action on tumor cells, such as inhibiting tumor cell proliferation and inducing tumor cell apoptosis, and the second is mediated by indirect effects on tumor cells, such as by regulating the body's immune function and inhibiting tumor angiogenesis, among other ways. [6][7][8] Rapeseed peptide is mainly the product of rapeseed protein obtained by acid hydrolysis, protease hydrolysis or microbial fermentation. Small peptides can be directly absorbed by the intestinal tract, which is faster and more bioactive than amino acids of the same content and composition.…”
Section: Introductionmentioning
confidence: 99%